Open Access Monitor - DK (OAM-DK): Indsamling, dokumentation og administration af publiceringsudgifter til Open Access i Danmark - Svendsen, Michael; Hansen, Claus Rosenkrantz; Hansen, Dorte (2019)
In a changing landscape of new Open Access modes, Denmark has adopted a so-called green Open Access strategy, according to which publications must be kept largely free of charge and publications must be archived in institutional repositories.Even so, Danish universities spend significant financial resources on Open Access publishing. Substantial fees are being paid to publish via the golden route in Open Access journals, but also in subscription-based journals via the hybrid model. The latter is especially interesting considering the practice of double-dipping, where universities not only pay for the right-to-read (via the national e-license portfolios) but also for the right-to-publish (via publication fees).This raises the question of the scale of resources being spent on Open Access publishing by Danish universities. This DEFF project follows similar efforts in the UK, Sweden, Norway, Germany and the Netherlands, monitoring how much is being spent on gold and hybrid publishing by Danish universities. The approach has been to identify the publishing ecology of Open Access and derived financial costs. Since it is difficult to gather invoice data, an economic model has been developed to estimate the total cost of publication at Danish universities.Results show that both gold and hybrid publishing practices and expenses related to Open Access publishing in the Danish universities are increasing substantially and that monitoring efforts are required.An executive summary with ten results and recommendations has been produced and is available here: https://zenodo.org/record/1544953.Read more about the project: https://bit.ly/oam-dk